Hydrochemistry of Surface and Groundwater in Parts of Birnin Kebbi Northwestern Nigeria - Abdulganiyu, Y.; Oresajo, B. S.; AbdulKarim, M.; Phillips, O. A.; Ibrahim, H.; Abdulfatah, T. A.; Yakubu, H.; Zainab, H.; Sadiya, M.; Nasiru, A.; Mahmud, I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
A hydro-chemical investigation of drinking water sources in Birnin Kebbi Old Town and its environs, in northwestern Nigeria, was carried out to determine the potability and suitability of the groundwater for domestic and agricultural uses. Twenty-three water samples were collected from these communities, and their physical and chemical parameters, such as electrical conductivity, total dissolved solids, pH, and temperature, were evaluated. Both the chemical and heavy metal analyses were conducted at the Multi-User Laboratory, Usmanu Danfodiyo University, Sokoto. The results obtained indicated that physical parameters like TDS and EC and chemical parameters like Mg2+, Ca2+ and HCO32- are high, while Cr2+, Fe2+, Ni, and Pb2+ have values that are below the NSDWQ recommended limits. While Na2+, Cu2+, Cl-, and NO3- have values far below the NSDWQ set limit, The Schoeller and Piper diagrams show the dominant water type in the study area to be Ca-Mg-HCO3. However, the Gibbs plot shows the dominant source of the water to be the precipitation domain due to the dissolution of carbonate rocks, while the Wilcox diagram shows that all the water samples in the study area have low salinity. Application of Nemerow’s pollution index method shows that the majority of the sampling locations displayed high NPI values, especially for Ni2+ and Pb2+. The NPI Ni2+ values for eleven (11) out of twenty-three samples, making up 47.83%, have NPI values that range from 7.53 to 90.01, making them unsuitable for drinking purposes. The NPI values for Pb2+ for six (6) samples, making up about 26.09%, have high NPI values that range from 36.37 to 172.56, depicting a high level of pollution.